Apolipoprotein E Levels in the Cerebrospinal Fluid of North Indian Patients With Alzheimer's Disease. (May 2013) - Kandimalla, Ramesh J. L.; Wani, Willayat Yousuf; Anand, R.; Kaushal, Alka; Prabhakar, Sudesh; Grover, Vinod K.; Bharadwaj, Neerja; Jain, Kajal; Gill, Kiran Dip
The etiology of Alzheimer's disease (AD) is multifactorial involving both genetic and environmental factors. Apolipoprotein E ( ApoE ) gene plays a pivotal role in risk and age of onset of AD. Although it is broadly accepted that ApoE genotype is linked to the pathogenesis of AD, there are still controversial results regarding the association of ApoE levels in cerebrospinal fluid (CSF) with the occurrence of AD. Some studies have shown a positive correlation between CSF ApoE levels and AD, whereas others showed no link. In this study, we measured ApoE levels to assess the usefulness of CSF ApoE as a diagnostic marker of AD by comparing the levels in 3 patient groups and in control participants. No significant difference was observed in CSF ApoE concentrations between the patients with AD and the controls. So, it appears that CSF ApoE measurement does not offer any diagnostic advantage for AD.